Hubungan Antara Persepsi Dukungan Sosial dengan Tingkat Stres Kompetisi pada Atlet Sepatu Roda - muhammad oky andriyanto; Anung Priambodo; Irmantara Subagio; moh amrullah albaitomi (Universitas Negeri Yogyakarta, 2025)
Abstract This study investigates the relationship between perceived social support and competition stress levels in roller skate athletes. Competition stress is a common psychological phenomenon experienced by athletes and has the potential to impact both performance and mental well-being. Social support, which may come from sources such as coaches, teammates, family, and friends, is hypothesized to be a protective factor that can mitigate the negative effects of stress. Using a quantitative correlational approach, this research aims to test the hypothesis that there is a significant negative relationship between perceived social support and competition stress levels among roller skate athletes. The results indicate that higher levels of perceived social support are significantly correlated with lower levels of competition stress. These findings highlight the importance of social support in stress management strategies for roller skate athletes and offer practical implications for the development of psychological interventions focused on strengthening athletes’ support networks.